2007
DOI: 10.1111/j.1469-7580.2006.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Which spinal levels are identified by palpation of the iliac crests and the posterior superior iliac spines?

Abstract: The line joining the superior aspect of the iliac crests posteriorly (the intercristal line) is commonly stated to cross the midline at the L4 or L4 -5 spinal level on imaging. This study aimed to assess the spinal level identified through identifies different spinal levels to those identified by imaging and that both methods should be regarded as different instruments. In the clinical situation, it may be more appropriate to consider that palpation of the intercristal line is a guide for identifying the L3 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 17 publications
5
84
1
1
Order By: Relevance
“…In that study, the interspaces were identified by palpation from C7 to the sacrum. Our alternate hypothesis was based on the study by Chakraverty et al, 15 in which they determined, by means of fluoroscopy, that the palpated intercristal line in the female subgroup was above L4-L5 in 85.7% of cases. Assuming a two-sided type I error of 5% and a type II error of 10%, a sample size of 40 subjects with 90% power was needed to demonstrate that the intercristal line intersects the lumbar spine in term pregnant women in a more cephalad segment than the L4-L5 interspace.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the interspaces were identified by palpation from C7 to the sacrum. Our alternate hypothesis was based on the study by Chakraverty et al, 15 in which they determined, by means of fluoroscopy, that the palpated intercristal line in the female subgroup was above L4-L5 in 85.7% of cases. Assuming a two-sided type I error of 5% and a type II error of 10%, a sample size of 40 subjects with 90% power was needed to demonstrate that the intercristal line intersects the lumbar spine in term pregnant women in a more cephalad segment than the L4-L5 interspace.…”
Section: Discussionmentioning
confidence: 99%
“…T uffier çizgisi, her iki iliak kristanın en yüksek noktalarını birleştiren, genellikle 4. lomber (L4) vertebranın gövdesi veya 4. lomber ve 5. lomber vertebralar arasından (L4-L5) geçen çizgidir (1). Rutin klinik uygulamada nöroaksiyal blok uygulanacak hastalarda Tuffier çizgisinin geçtiği intervertebral aralık belirlenerek, işlem bu seviyeden yapılır.…”
Section: Introductionunclassified
“…The intercristal line is defined as the line joining the superior aspect of the iliac crests posteriorly (2). Chakraverty et al suggests that clinical palpation of the intercristal line commonly identifies the L3 or L3-4 spinal levels rather than the L4 or L4-5 levels, particularly in females and patients with higher body mass indices (3). On the other hand, the intercristal line is commonly identified as the L4-5 spinal level on radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The intercristal line was determined and based on it, the pathology related spinous process or interspinous space corresponding to the spinal pathology was estimated and marked using a surgical ink marker. The intercristal line was taken to be the L4-5 spinal level in a young thin male and L3-4 spinal level in all other patients (3). Palpable deformities such as widening of the interspinous space in patients with traumatic flexion distraction injuries and focal kyphosis as seen on pre-operative imaging were adjuncts used to further refine this process.…”
Section: Pathology Related Spine Level Localizationmentioning
confidence: 99%